Pharmacokinetic equivalence and comparative safety, tolerability, and immunogenicity of Biocon's ustekinumab (Bmab-1200) with EU-approved and US-licensed reference ustekinumab in healthy subjects: results from the Study to Test pharmacokinetic BioEquivalence of BiosimiLar ustekinumab to SteLARa (STELLAR-1) - Ackroyd, Jonathan; Deodhar, Sarika S; Loganathan, Subramanian; Singh, Gursharan; Marwah, Ashwani; Kumar, Kuldeep; Panda, Jayanti; Athalye, Sandeep Nilkanth (Expert opinion on investigational drugs, 2025)
This study assessed the pharmacokinetics (PK) equivalence, safety, tolerability, and immunogenicity of Bmab-1200 versus the reference product ustekinumab (EU-approved and US-licensed Stelara). This 20-week, randomized, double-blind, three-arm, parallel-design, Phase-1 study enrolled healthy male and female subjects ( = 258; 18-55 years). A single, 45-mg subcutaneous injection of Bmab-1200, EU-approved Stelara, or US-licensed Stelara was administered in a 1:1:1 ratio. Subject stratification was performed by ethnicity, body weight range, and gender. Primary PK endpoints included AUC and C . Secondary endpoints included additional PK parameters, immunogenicity, and safety and tolerability. All three pairwise comparisons of Bmab-1200 versus US-Stelara, Bmab-1200 versus EU-Stelara, and US-Stelara versus EU-Stelara were equivalent for AUC (90% confidence intervals [CIs] of the geometric least squares mean [GLSM] ratio: 0.9975-1.1657, 0.9959-1.1685, and 0.9223-1.0921, respectively) and C (90% CIs of the GLSM ratio: 0.9478-1.0732, 0.9136-1.0376, and 0.9012-1.0267, respectively). All secondary analyses supported the primary results. Three-way PK equivalence between Bmab-1200, US-Stelara, and EU-Stelara was demonstrated. A single, 45-mg dose of Bmab-1200 was safe and well tolerated, and, overall, the number of AEs was similar among the groups. Diversity limited to White and Japanese groups did not impact the study results. This study was registered with www.isrctn.com; identifier: ISRCTN11424009.